THE EFFECT OF WORK CULTURE, WORK ENVIRONMENT AND COMPENSATION ON JOB SATISFACTION AND THEIR IMPACT ON TELEVISION MEDIA EMPLOYEE LOYALTY IN JAKARTA - Rani Rani; Wahyu Indrarti; Faizal Roni (SEAN Institute, 2022)
This study aimed to examine the effect of work culture, work environment, and compensation on job satisfaction and their effect on employee loyalty. This research is quantitative, and the research was conducted in Jakarta on television media workers, using a sampling technique in this study used is Purposive Sampling, with television employee's criteria and willingness to fill out a questionnaire. Collecting data using a Likert scale questionnaire, and from the data, collection results obtained 68 respondents who were willing to fill out the questionnaire. The collected data is processed using SmartPLS software. Based on the research results, work culture has a significant effect on job satisfaction, compensation has a significant effect on job satisfaction, work culture has a significant effect on loyalty, the work environment has a significant effect on loyalty, job satisfaction has a significant effect on loyalty, 8. Work culture has a positive effect on loyalty through job satisfaction, the Work environment has a negative effect on loyalty through job satisfaction, and compensation has a positive effect on loyalty through job satisfaction.